Numerical Modelling of Polycrystalline Diamond device for Advanced Sensor Design. (2016) - Morozzi, Arianna; Passeri, Daniele; Kanxheri, Keida; Servoli, Leonello; Sciortino, Silvio; Lagomarsino, Stefano
Abstract: Technology Computer Aided Design (TCAD) simulation tools are routinely adopted within the design flow of semiconductor devices to simulate their electrical characteristics. However, the device level simulation of diamond is not straightforward within the state-of-the-art TCAD tools. Physical models have to be specifically formulated and tuned for single-crystal CVD (scCVD) and polycrystalline (pcCVD) diamond in order to account for, among others, incomplete ionization, intrinsic carrier free material, dependences of carrier transport on doping and temperature, impact ionization, traps and recombination centers effects. In this work, we propose the development and the application of a numerical model to simulate the electrical characteristics of polycrystalline diamond conceived for sensors fabrication. The model is based on the introduction of an articulated, yet physically based, picture of deep-level defects acting as recombination centers and/or trap states. This approach fosters the exploration and optimization of innovative semiconductor devices conjugating the capabilities of CMOS electronics devices and the properties of diamond substrates, e.g. for biological sensor applications or single particle detectors for High Energy Physics experiments.